Physiological and transcriptome profiling revealed defense networks during Cladosporium fulvum and tomato interaction at the early stage - Peng, Rong; Sun, Sheng; Li, Na; Kong, Lingjuan; Chen, Zhifeng; Wang, Peng; Xu, Lurong; Wang, Hehe; Geng, Xueqing (Frontiers in Plant Science, 2022)
Tomato leaf mold caused by Cladosporium fulvum (C. fulvum) is a serious fungal disease which results in huge yield losses in tomato cultivation worldwide. In our study, we discovered that ROS (reactive oxygen species) burst was triggered by C. fulvum treatment in tomato leaves. RNA-sequencing was used to identify differentially expressed genes (DEGs) induced by C. fulvum inoculation at the early stage of invasion in susceptible tomato plants. Gene ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases were used to annotate functions of DEGs in tomato plants. Based on our comparative analysis, DEGs related to plant-pathogen interaction pathway, plant hormone signal transduction pathway and the plant phenylpropanoid pathway were further analyzed. Our results discovered that a number of core defense genes against fungal invasion were induced and plant hormone signal transduction pathways were impacted by C. fulvum inoculation. Further, our results showed that SA (salicylic acid) and ABA (abscisic acid) contents were accumulated while JA (jasmonic acid) content decreased after C. fulvum inoculation in comparison with control, and quantitative real-time PCR to detect the related expression of genes involved in SA, ABA and JA signaling pathway further confirmed our results. Together, results will contribute to understanding the mechanisms of C. fulvum and tomato interaction in future.